2017
DOI: 10.1371/journal.pone.0187268
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic difference in bovine blastocysts following vitrification and slow freezing at morula stage

Abstract: Cryopreservation is known for its marked deleterious effects on embryonic health. Bovine compact morulae were vitrified or slow-frozen, and post-warm morulae were cultured to the expanded blastocyst stage. Blastocysts developed from vitrified and slow-frozen morulae were subjected to microarray analysis and compared with blastocysts developed from unfrozen control morulae for differential gene expression. Morula to blastocyst conversion rate was higher (P < 0.05) in control (72%) and vitrified (77%) than in sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 68 publications
2
26
0
Order By: Relevance
“…Knowledge so far indicates that suboptimal conditions during ART may induce embryonic stress responses and affect embryo viability [ 10 , 11 ]. In addition, cryopreservation is known for its harmful impacts on embryonic health, placing embryos at risk from a variety of types of cryoinjury during temperature and phase transitions [ 18 , 27 ]. Such survival impairment is in agreement with previous studies performed in rabbits, where manipulations of either fresh or vitrified embryos resulted in negative developmental effects both under in vitro conditions and in vivo [ 22 , 23 , 26 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge so far indicates that suboptimal conditions during ART may induce embryonic stress responses and affect embryo viability [ 10 , 11 ]. In addition, cryopreservation is known for its harmful impacts on embryonic health, placing embryos at risk from a variety of types of cryoinjury during temperature and phase transitions [ 18 , 27 ]. Such survival impairment is in agreement with previous studies performed in rabbits, where manipulations of either fresh or vitrified embryos resulted in negative developmental effects both under in vitro conditions and in vivo [ 22 , 23 , 26 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also know that, vitri cation negatively impacts porcine embryo quality, augmenting levels of apoptosis [19,20] or impairing ultrastructure [21]. Vitri cation has been found to cause modi cations in the embryo gene expression in several species [22][23][24][25][26][27]; however, the consequences of vitri cation on gene expression of mammalian embryos are poorly known.…”
Section: Introductionmentioning
confidence: 99%
“…General transcriptome experiments of vitri ed-warmed have been done only in bovine. Vitri cation of in vitro-produced (IVP) bovine embryos caused overexpression of apoptosis-related genes [25] and the repression of genes involved in cell differentiation, cell adhesion and metabolism of lipids [28]. It has been also demonstrated that vitri cation modi ed expression of genes related to stress response [29] in both IVP and in vivo-derived bovine blastocysts.…”
Section: Introductionmentioning
confidence: 99%
“…Differentially expressed genes (DEGs) between frozen and vitrified (Larman et al, 2011;Stinshoff et al, 2011) and between fresh and vitrified (Leme et al, 2016) IVP embryos have already been described. According to Gupta et al (2017), vitrified morulae exhibited improved cryosurvival compared to those obtained using the slow freezing method. However, an altered transcriptional profile related to the impairment of implantation and placentation in the uterus was revealed in blastocysts derived from vitrified morulae (Gupta et al, 2017).…”
mentioning
confidence: 99%
“…According to Gupta et al (2017), vitrified morulae exhibited improved cryosurvival compared to those obtained using the slow freezing method. However, an altered transcriptional profile related to the impairment of implantation and placentation in the uterus was revealed in blastocysts derived from vitrified morulae (Gupta et al, 2017).…”
mentioning
confidence: 99%